Enhancing learner self-efficacy in interviews through ChatGPT-based practice: A preliminary study - Bernadette Tobi; Eugenia Ida Edward (2025)
Developing English speaking skills in Malaysia remains a significant challenge, particularly among undergraduates who obtained Malaysian University English Test (MUET) band 3.5 or below. The predominantly non-native English-speaking environment offers limited lexical support, making it difficult for students to use the target language fluently, proficiently, and confidently. However, advancements in technology and the emergence of ChatGPT present a promising opportunity to assist these students with their interview assessment in English. It is a common belief that technology, especially Artificial Intelligence tools, can enhance language production and boost confidence in using the target language. This study examines the impact of ChatGPT-generated suggested responses to common interview questions within an English for Occupational Purposes assessment. Students were taught to create specific prompts to customize ChatGPT-generated dialogues based on requirements mentioned in their chosen job advertisements and the resumes that they generated. The focus was on language competence, quality of answers, and confidence level of the experimental group of students required to use ChatGPT assistance compared to students in the control group. The assessment results showed no significant differences between the experimental and control groups, suggesting that the use of ChatGPT does not necessarily guarantee better performance in students’ job interview assessments.